JAGAT HEROIK PEREMPUAN - Ayub Wahyudin (Muwazah, 2009)
Women in the tradition of the heroic world of the archipelago has entered a â€œdecisiveâ€ and â€œthreateningâ€ presence of people for some people. As a result of rebel attacks around the world pierced by gender, women should have a prominent place. But there are efforts to theological, sociological, and culture that strives to create a new birth of compliance â€œâ€ and â€œspiritual obedienceâ€ to the world of gender, with women as abdun needs (subject). Compliance is sometimes a real tangible in silence as a zombie â€œ-a woman who in herâ€ by the attacks that are considered absolute doctrine. Not a few of them accept injustice, alienation, and even violence that never imagined before. It should be emphasized, that heroic woman in the world there are a number of ideas that always lead to wrong interpretation and the process of exclusion (exemption) for women.